2018
DOI: 10.4183/aeb.2018.192
|View full text |Cite
|
Sign up to set email alerts
|

The Romanian Version of the Thyroid-Related Patient-Reported Outcomes Thypro and Thypro-39. Translation and Assessment of Reliability and Crosscultural Validity

Abstract: Background. ThyPRO is a recently developed thyroid-specific quality of life (QoL) questionnaire applicable to patients with benign thyroid disorders(BTD). The aim of the present study was to translate ThyPRO and ThyPRO-39 into Romanian, and to evaluate reliability and cross-cultural validity.Methods. Standard methodology for translation and linguistic validation of patient-reported outcomes (PRO) was applied. The questionnaire was completed by 130 patients with benign thyroid diseases seen at Department of End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…These subtle differences might explain the scale’s comparatively low alpha. Interestingly, the Spanish version of the ThyPRO-39 also suffered from the low alpha in the cosmetic complaints scale ( 8 ), but adaptations into other languages did not ( 7 , 20 ). These circumstances make it difficult to determine whether there is a problem with the scale itself or its German adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These subtle differences might explain the scale’s comparatively low alpha. Interestingly, the Spanish version of the ThyPRO-39 also suffered from the low alpha in the cosmetic complaints scale ( 8 ), but adaptations into other languages did not ( 7 , 20 ). These circumstances make it difficult to determine whether there is a problem with the scale itself or its German adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetic complaints scale ( 8), but adaptations into other languages didn't (7,20). These circumstances make it difficult to determine whether there is a problem with the scale itself or its German adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was comparable with other reliability studies. One study using a Romanian version of the ThyPRO 30 found that the Cronbach α coefficients ranged from 0.78 to 0.93, and another using a Serbian version found that they ranged from 0.83 to 0.95. 31 …”
Section: Discussionmentioning
confidence: 99%
“…It was first created in Denmark by Dr. Torquil Watt and colaborators from Ringhospitalet University Hospital of Copenhagen [6]. Following several international studies this instrument was validated and translated into Romanian language [7]. The questionnaire contains a total of 85 questions grouped into 13 scales which cover the following: physical symptoms, mental symptoms, general well being, social life and one final question regarding quality of life as a whole.…”
Section: Methodsmentioning
confidence: 99%